Nickel phosphide / cadmium sulfide heterojunction nanorod array composite material and preparation method thereof
The cadmium sulfide nanorod array was grown by hydrothermal method and nickel phosphide particles were epitaxially grown on its surface to form a nickel phosphide/cadmium sulfide heterojunction nanorod array composite material, which solved the problems of poor crystallinity of cadmium sulfide nanorod array and high toxicity during phosphating in the prior art, and achieved efficient and stable photoelectrochemical performance.
Patent Information
- Application Number
- CN202510044244.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-11
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, the crystallinity of cadmium sulfide nanospheres is poor, resulting in low separation and transmission efficiency of photogenerated carriers, and the white phosphorus used during phosphating is highly toxic and the reaction conditions are harsh, which may destroy the photocatalyst and introduce residual phosphorus precursors.
The cadmium sulfide nanorod array was grown by hydrothermal method, and nickel phosphide particles were epitaxially grown on its surface by solvothermal method to form a nickel phosphide/cadmium sulfide heterojunction nanorod array composite. This method is simple and easy to implement, green and environmentally friendly, and the loading of nickel phosphide can be adjusted by regulating the amount of sodium hypophosphite.
The photoelectrochemical performance and stability of the cadmium sulfide nanorod array is improved, the light absorption and photochemical reaction active sites are enhanced, the photocorrosion of cadmium sulfide is reduced, and the load of nickel phosphide can be adjusted to optimize the photoelectric performance.
Smart Images

Figure CN119793498A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic photoelectric materials, and particularly relates to a nickel phosphide / cadmium sulfide heterojunction nanorod array composite material and a preparation method thereof. Background Art
[0002] The consumption of fossil fuels and the serious pollution caused by them have led to a global energy and environmental crisis. Therefore, it is becoming increasingly important to find renewable energy and various alternative energy sources to fossil fuels. Solar energy is expected to replace fossil fuels to solve the global energy crisis due to its abundant sources, large radiation, cleanliness and sustainability. Among them, it is of great practical significance to develop efficient and economical photoelectrochemical conversion (PEC) technology to convert light energy into chemical energy and achieve a continuous supply of hydrogen energy. As one of the ideal materials for PEC photoelectric solar level, semiconductor cadmium sulfide has the advantages of narrow band gap, suitable valence band position and low cost. Nickel phosphide can form a heterojunction structure with cadmium sulfide, effectively separate and transmit photogenerated carriers, and can also form a protective layer on the surface of cadmium sulfide to reduce the photocorrosion effect of cadmium sulfide itself and effectively improve its stability under light. Therefore, constructing heterojunctions and doping heterojunctions are considered to be effective methods to enhance the photoelectric properties of CdS.
[0003] In the prior art, Zhen (Zhen W, Ning X, et al. Applied Catalysis B: Environmental, 2018, 221: 243-257) et al. prepared cadmium sulfide nanospheres coated with Ni2P shells, but the cadmium sulfide nanospheres prepared by this method have poor crystallinity, resulting in low separation and transmission efficiency of photogenerated carriers, and the phosphating process has high toxicity of white phosphorus and harsh reaction conditions. The harsh phosphating conditions may destroy the photocatalyst and may introduce residual phosphorus precursors into the final product. Therefore, this process is relatively complicated and deviates from the concept of green chemistry. In the invention patent "A method for producing hydrogen from methanol" with publication number CN112479158A, a method for preparing a nickel phosphide / cadmium sulfide photocatalyst is given. However, the product prepared by this method has no crystal growth orientation, many crystal defects, and poor performance in terms of photoelectrochemical performance stability. In the 5h cycle test, the internal hydrogen production efficiency shows a steady downward trend. In the invention patent "A method for preparing a nickel phosphide co-catalyst by photodeposition on cadmium sulfide" with publication number CN 110813335A, a method for preparing a cadmium sulfide / nickel phosphide visible light catalyst is given. However, the hydrothermal reaction time of this method is long, and long-term illumination with a xenon lamp is required. The process is relatively complex, the energy consumption is large, and it deviates from the concept of green chemistry and is not conducive to industrial production. In the invention patent "Transition metal element doped and cadmium sulfide loaded transition metal phosphide photocatalytic material with sulfur vacancies and its preparation method" with publication number CN 114471639A, a transition metal element doped and cadmium sulfide loaded transition metal phosphide photocatalytic material with sulfur vacancies is prepared. The method has complicated steps, and the phosphating step depends on solid-phase reaction with sodium hypophosphite. The phosphating process may destroy the photocatalyst and produce toxic gases. The steps are complicated, the energy consumption is large, and it deviates from the concept of green chemistry. Summary of the invention
[0004] In view of the above-mentioned deficiencies of the prior art, the present invention provides a nickel phosphide / cadmium sulfide heterojunction nanorod array composite material and a preparation method thereof. The method is simple and easy to implement, green and environmentally friendly, and the obtained material has good photoelectrochemical properties.
[0005] To achieve the above object, the present invention adopts the following technical solution: A nickel phosphide / cadmium sulfide heterojunction nanorod array composite material, wherein the loading amount of the nickel phosphide is 1wt%-5wt%.
[0006] The preparation method of the nickel phosphide / cadmium sulfide heterojunction nanorod array composite material comprises the following steps: (1) Preparation of cadmium sulfide nanorod arrays: Cadmium nitrate, thiourea, L-cysteine and deionized water were mixed evenly, transferred to a polytetrafluoroethylene reactor, and immersed in the pretreated conductive glass FTO substrate. After hydrothermal reaction, the substrate was cooled to room temperature, and the conductive glass FTO substrate was taken out, cleaned, dried, and then annealed to obtain an FTO substrate with cadmium sulfide nanorod arrays grown on the surface. (2) Preparation of nickel phosphide / cadmium sulfide heterojunction nanorod array composite material: dissolve the phosphorus source, nickel source and sodium borohydride in ethylenediamine, stir evenly and transfer to a hydrothermal reactor, immerse the FTO substrate with cadmium sulfide nanorod array grown on the surface obtained in step (1), cool to room temperature after solvothermal reaction, take out, wash and dry.
[0007] Furthermore, the molar ratio of cadmium nitrate, thiourea and L-cysteine used in step (1) is 1:1:0.6.
[0008] Furthermore, in step (1), the pretreatment method of the conductive glass FTO substrate is to first ultrasonically clean the conductive glass FTO substrate with a mixed solution of acetone, isopropanol and deionized water in a volume ratio of 1:1:1 for 60 minutes, then ultrasonically clean it with deionized water for 60 minutes, and dry it at 60°C for later use.
[0009] Furthermore, the hydrothermal reaction in step (1) is first carried out at 160°C for 1 h, then the temperature is raised to 180°C and the reaction is continued for 2.5 h.
[0010] Furthermore, the annealing treatment in step (1) is performed by heating the temperature to 400°C at a rate of 5°C / min and keeping the temperature for 1 hour.
[0011] Furthermore, the phosphorus source in step (2) is sodium hypophosphite.
[0012] Furthermore, the nickel source in step (2) is nickel chloride.
[0013] Furthermore, the molar ratio of the phosphorus source, the nickel source and the sodium borohydride used in step (2) is (5-25):1.4:52.
[0014] Furthermore, the temperature of the solvent thermal reaction in step (2) is 160° C. and the time is 24 hours.
[0015] The present invention first grows a cadmium sulfide nanorod array on a pretreated FTO conductive glass by a hydrothermal method, and then epitaxially grows nickel phosphide particles on the surface of cadmium sulfide by a solvothermal method, thereby forming a nickel phosphide / cadmium sulfide heterojunction nanorod array composite material. The formation of the nickel phosphide / cadmium sulfide heterojunction increases the active sites, accelerates the separation of photogenerated carriers, and further improves the photoelectric performance and stability of the cadmium sulfide nanorod array material, so that it can be used in the field of photoelectrocatalysis. At the same time, the loading amount of nickel phosphide can be adjusted by adjusting the dosage of sodium hypophosphite, further improving the photoelectrochemical performance of the nickel phosphide / cadmium sulfide heterojunction nanorod array composite material.
[0016] Compared with the prior art, the advantages of the present invention are: (1) The constructed cadmium sulfide nanorod array has good crystallization performance, which is conducive to the transmission of photocurrent.
[0017] (2) The constructed ordered array of nickel phosphide / cadmium sulfide heterojunctions can increase the photochemical reaction active sites, enhance light absorption, and effectively reduce the photocorrosion of cadmium sulfide. The phosphating route is safe, mild, and effective, and can effectively control the composition of the product and establish good contact between Ni2P and cadmium sulfide nanorod arrays.
[0018] (3) By controlling the loading amount of nickel phosphide, the photoelectric performance of the nickel phosphide / cadmium sulfide heterojunction nanorod array can be effectively improved. The appropriate amount of nickel phosphide also has a synergistic effect of promoting charge separation, which can reduce the recombination of photogenerated electrons and holes, thereby greatly improving the PEC performance of the composite material.
[0019] (3) Low equipment requirements: The synthesis reaction of the present invention does not exceed 180°C and can be completed in a hydrothermal kettle, without the need for input of additional energy such as electricity or heat, thus saving energy and reducing emissions.
[0020] (4) Low cost, high efficiency, and more environmentally friendly: The present invention does not require the use of expensive instruments and chemical reagents during the preparation process, which is in line with the concept of environmental protection and has significant advantages in terms of economy, efficiency, and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope image of the nickel phosphide / cadmium sulfide heterojunction nanorod array prepared in Example 1.
[0022] Figure 2 This is a scanning electron microscope image of the nickel phosphide / cadmium sulfide heterojunction nanorod array prepared in Example 2.
[0023] Figure 3 This is a scanning electron microscope image of the nickel phosphide / cadmium sulfide heterojunction nanorod array prepared in Example 3.
[0024] Figure 4 This is a scanning electron microscope image of the nickel phosphide / cadmium sulfide heterojunction nanorod array prepared in Example 4.
[0025] Figure 5 This is a scanning electron microscope image of the nickel phosphide / cadmium sulfide heterojunction nanorod array prepared in Example 5.
[0026] Figure 6 X-ray diffraction patterns of nickel phosphide / cadmium sulfide heterojunction nanorod arrays with different nickel phosphide loadings prepared in Examples 1 to 5.
[0027] Figure 7 The current-time (it) curves of nickel phosphide / cadmium sulfide heterojunction nanorod arrays with different nickel phosphide loadings prepared in Examples 1 to 5 are shown.
[0028] Figure 8 This is a graph showing the photoelectric conversion efficiency (ABPE) of the nickel phosphide / cadmium sulfide heterojunction nanorod array prepared in Example 3.
[0029] Fig. 9 The incident photon-to-photoelectric conversion efficiency (IPCE) curves of the nickel phosphide / cadmium sulfide heterojunction nanorod arrays with different nickel phosphide loadings prepared in Examples 1 to 5 are shown.
[0030] Fig.10 The current-time (it) curves of the nickel phosphide-loaded nickel phosphide / cadmium sulfide heterojunction nanorod array prepared in Example 3 and the nickel phosphide / cadmium sulfide heterojunction nanorod array prepared by the thermal phosphorus method in the comparative example. DETAILED DESCRIPTION
[0031] A nickel phosphide / cadmium sulfide heterojunction nanorod array composite material, the preparation of which comprises the following steps: (1) Pretreatment of the conductive glass FTO substrate: The conductive glass FTO substrate was first ultrasonically cleaned with a mixed solution of acetone, isopropanol and deionized water (1:1:1, v / v / v) for 60 min, then ultrasonically cleaned with deionized water for 60 min, and dried at 60 °C for later use; (2) Preparation of cadmium sulfide nanorod arrays: Cadmium nitrate, thiourea and L-cysteine were weighed in a molar ratio of 1:1:0.6, and after being mixed with deionized water, the mixed solution was transferred to a polytetrafluoroethylene reactor and immersed in the pretreated conductive glass FTO substrate. After hydrothermal reaction at 160 °C for 1 h, the temperature was raised to 180 °C and the reaction was continued for 2.5 h. The substrate was then cooled to room temperature. The conductive glass FTO substrate was taken out and rinsed with deionized water and ethanol to remove surface impurities and organic solvents. It was then dried in a vacuum oven at 60 °C, and then heated to 400 °C at a rate of 5 °C / min and kept warm for 1 h to obtain an FTO substrate with cadmium sulfide nanorod arrays grown on the surface. (3) Preparation of nickel phosphide / cadmium sulfide heterojunction nanorod array composite material: Sodium hypophosphite, nickel chloride and sodium borohydride were dissolved in ethylenediamine in a molar ratio of (5-25):1.4:52, stirred evenly and transferred to a hydrothermal reactor, immersed in the FTO substrate with cadmium sulfide nanorod array grown on the surface obtained in step (2), and subjected to solvothermal reaction at 160°C for 24 hours, cooled to room temperature, taken out and rinsed with deionized water and ethanol respectively to remove surface impurities and organic solvents, and then dried in a vacuum oven at 60°C to obtain a nickel phosphide / cadmium sulfide heterojunction nanorod array composite material with a nickel phosphide loading of 1wt%-5wt%.
[0032] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0033] Example 1 (1) Pretreatment of FTO: FTO was first immersed in a mixed solution of acetone, isopropanol, and deionized water (1:1:1, v / v / v), ultrasonically cleaned for 60 min, then immersed in deionized water, ultrasonically cleaned for 60 min, and dried at 60 °C for later use.
[0034] (2) 148.7 mg of cadmium nitrate, 36.5 mg of thiourea and 34.9 mg of L-cysteine were mixed with 20 mL of deionized water and then transferred to a polytetrafluoroethylene reactor. The conductive surface of FTO was placed at a certain angle against the inner wall of the polytetrafluoroethylene reactor with the conductive surface facing downward. The reaction was carried out at 160°C for 1 h, and then the temperature was raised to 180°C and the reaction was continued for 2.5 h. After the reaction was completed, the FTO was cooled to room temperature with water. The FTO was taken out and rinsed with deionized water and ethanol respectively to remove surface impurities and organic solvents. It was then dried at 60°C in a vacuum oven and then heated to 400°C at 5°C / min in a tubular furnace. The reaction was kept at this temperature for 1 h to obtain FTO with cadmium sulfide nanorod arrays grown on the surface.
[0035] (3) Dissolve 47.3 mg of sodium hypophosphite, 18.32 mg of nickel chloride and 200 mg of sodium borohydride in 20 mL of ethylenediamine, stir well and transfer to a hydrothermal reactor. Place the FTO with cadmium sulfide nanorod arrays grown on the surface obtained in step (2) in a polytetrafluoroethylene reactor at an angle with the conductive surface facing downward. React at 160 °C for 24 h. After the reaction is completed, cool to room temperature with water. Take out the FTO, rinse with deionized water and ethanol respectively, and vacuum dry at 60 °C to obtain a nickel phosphide / cadmium sulfide heterojunction nanorod array composite material with a Ni2P loading of 1%.
[0036] Example 2 (1) Pretreatment of FTO: FTO was first immersed in a mixed solution of acetone, isopropanol, and deionized water (1:1:1, v / v / v), ultrasonically cleaned for 60 min, then immersed in deionized water, ultrasonically cleaned for 60 min, and dried at 60 °C for later use.
[0037] (2) 148.7 mg of cadmium nitrate, 36.5 mg of thiourea and 34.9 mg of L-cysteine were mixed with 20 mL of deionized water and then transferred to a polytetrafluoroethylene reactor. The conductive surface of FTO was placed at a certain angle against the inner wall of the polytetrafluoroethylene reactor with the conductive surface facing downward. The reaction was carried out at 160°C for 1 h, and then the temperature was raised to 180°C and the reaction was continued for 2.5 h. After the reaction was completed, the FTO was cooled to room temperature with water. The FTO was taken out and rinsed with deionized water and ethanol respectively to remove surface impurities and organic solvents. It was then dried at 60°C in a vacuum oven and then heated to 400°C at 5°C / min in a tubular furnace. The reaction was kept at this temperature for 1 h to obtain FTO with cadmium sulfide nanorod arrays grown on the surface.
[0038] (3) Dissolve 94.85 mg of sodium hypophosphite, 18.32 mg of nickel chloride and 200 mg of sodium borohydride in 20 mL of ethylenediamine, stir well and transfer to a hydrothermal reactor. Place the FTO with cadmium sulfide nanorod arrays grown on the surface obtained in step (2) in a polytetrafluoroethylene reactor at an angle with the conductive surface facing downward. React at 160 °C for 24 h. After the reaction is completed, cool to room temperature with water. Take out the FTO, rinse with deionized water and ethanol respectively, and vacuum dry at 60 °C to obtain a nickel phosphide / cadmium sulfide heterojunction nanorod array composite material with a Ni2P loading of 2%.
[0039] Example 3 (1) Pretreatment of FTO: FTO was first immersed in a mixed solution of acetone, isopropanol, and deionized water (1:1:1, v / v / v), ultrasonically cleaned for 60 min, then immersed in deionized water, ultrasonically cleaned for 60 min, and dried at 60 °C for later use.
[0040] (2) 148.7 mg of cadmium nitrate, 36.5 mg of thiourea and 34.9 mg of L-cysteine were mixed with 20 mL of deionized water and then transferred to a polytetrafluoroethylene reactor. The conductive surface of FTO was placed at a certain angle against the inner wall of the polytetrafluoroethylene reactor with the conductive surface facing downward. The reaction was carried out at 160°C for 1 h, and then the temperature was raised to 180°C and the reaction was continued for 2.5 h. After the reaction was completed, the FTO was cooled to room temperature with water. The FTO was taken out and rinsed with deionized water and ethanol respectively to remove surface impurities and organic solvents. It was then dried at 60°C in a vacuum oven and then heated to 400°C at 5°C / min in a tubular furnace. The reaction was kept at this temperature for 1 h to obtain FTO with cadmium sulfide nanorod arrays grown on the surface.
[0041] (3) Dissolve 142.2 mg of sodium hypophosphite, 18.32 mg of nickel chloride and 200 mg of sodium borohydride in 20 mL of ethylenediamine, stir well and transfer to a hydrothermal reactor. Place the FTO with cadmium sulfide nanorod arrays grown on the surface obtained in step (2) in a polytetrafluoroethylene reactor at an angle with the conductive surface facing downward. React at 160 °C for 24 h. After the reaction is completed, cool to room temperature with water. Take out the FTO, rinse with deionized water and ethanol respectively, and vacuum dry at 60 °C to obtain a nickel phosphide / cadmium sulfide heterojunction nanorod array composite material with a Ni2P loading of 3%.
[0042] Example 4 (1) Pretreatment of FTO: FTO was first immersed in a mixed solution of acetone, isopropanol, and deionized water (1:1:1, v / v / v), ultrasonically cleaned for 60 min, then immersed in deionized water, ultrasonically cleaned for 60 min, and dried at 60 °C for later use.
[0043] (2) 148.7 mg of cadmium nitrate, 36.5 mg of thiourea and 34.9 mg of L-cysteine were mixed with 20 mL of deionized water and then transferred to a polytetrafluoroethylene reactor. The conductive surface of FTO was placed at a certain angle against the inner wall of the polytetrafluoroethylene reactor with the conductive surface facing downward. The reaction was carried out at 160°C for 1 h, and then the temperature was raised to 180°C and the reaction was continued for 2.5 h. After the reaction was completed, the FTO was cooled to room temperature with water. The FTO was taken out and rinsed with deionized water and ethanol respectively to remove surface impurities and organic solvents. It was then dried at 60°C in a vacuum oven and then heated to 400°C at 5°C / min in a tubular furnace. The reaction was kept at this temperature for 1 h to obtain FTO with cadmium sulfide nanorod arrays grown on the surface.
[0044] (3) Dissolve 189.7 mg of sodium hypophosphite, 18.32 mg of nickel chloride and 200 mg of sodium borohydride in 20 mL of ethylenediamine, stir well and transfer to a hydrothermal reactor. Place the FTO with cadmium sulfide nanorod arrays grown on the surface obtained in step (2) in a polytetrafluoroethylene reactor at an angle with the conductive surface facing downward. React at 160 °C for 24 h. After the reaction is completed, cool to room temperature with water. Take out the FTO, rinse with deionized water and ethanol respectively, and vacuum dry at 60 °C to obtain a nickel phosphide / cadmium sulfide heterojunction nanorod array composite material with a Ni2P loading of 4%.
[0045] Example 5 (1) Pretreatment of FTO: FTO was first immersed in a mixed solution of acetone, isopropanol and deionized water (1:1:1, v / v / v), ultrasonically cleaned for 60 min, then immersed in deionized water for ultrasonic cleaning for 60 min, and dried at 60 °C for later use.
[0046] (2) 148.7 mg of cadmium nitrate, 36.5 mg of thiourea and 34.9 mg of L-cysteine were mixed with 20 mL of deionized water and then transferred to a polytetrafluoroethylene reactor. The conductive surface of FTO was placed at a certain angle against the inner wall of the polytetrafluoroethylene reactor with the conductive surface facing downward. The reaction was carried out at 160°C for 1 h, and then the temperature was raised to 180°C and the reaction was continued for 2.5 h. After the reaction was completed, the FTO was cooled to room temperature with water. The FTO was taken out and rinsed with deionized water and ethanol respectively to remove surface impurities and organic solvents. It was then dried at 60°C in a vacuum oven and then heated to 400°C at 5°C / min in a tubular furnace. The reaction was kept at this temperature for 1 h to obtain FTO with cadmium sulfide nanorod arrays grown on the surface.
[0047] (3) Dissolve 237.14 mg of sodium hypophosphite, 18.32 mg of nickel chloride and 200 mg of sodium borohydride in 20 mL of ethylenediamine, stir well and transfer to a hydrothermal reactor. Place the FTO with cadmium sulfide nanorod arrays grown on the surface obtained in step (2) in a polytetrafluoroethylene reactor at an angle with the conductive surface facing downward. React at 160 °C for 24 h. After the reaction is completed, cool to room temperature with water. Take out the FTO, rinse with deionized water and ethanol respectively, and vacuum dry at 60 °C to obtain a nickel phosphide / cadmium sulfide heterojunction nanorod array composite material with a Ni2P loading of 5%.
[0048] Comparative Example (1) Pretreatment of FTO: FTO was first immersed in a mixed solution of acetone, isopropanol and deionized water (1:1:1, v / v / v), ultrasonically cleaned for 60 min, then immersed in deionized water for ultrasonic cleaning for 60 min, and dried at 60 °C for later use.
[0049] (2) 148.7 mg of cadmium nitrate, 36.5 mg of thiourea and 34.9 mg of L-cysteine were mixed with 20 mL of deionized water and then transferred to a polytetrafluoroethylene reactor. The conductive surface of FTO was placed at a certain angle against the inner wall of the polytetrafluoroethylene reactor with the conductive surface facing downward. The reaction was carried out at 160°C for 1 h, and then the temperature was raised to 180°C and the reaction was continued for 2.5 h. After the reaction was completed, the FTO was cooled to room temperature with water. The FTO was taken out and rinsed with deionized water and ethanol respectively to remove surface impurities and organic solvents. It was then dried at 60°C in a vacuum oven and then heated to 400°C at 5°C / min in a tubular furnace. The reaction was kept at this temperature for 1 h to obtain FTO with cadmium sulfide nanorod arrays grown on the surface.
[0050] (3) 18.32 mg of nickel chloride was added to deionized water and stirred for 10 min. The mixture was transferred to a hydrothermal reactor. The FTO with cadmium sulfide nanorod arrays grown on the surface obtained in step (2) was placed obliquely in a polytetrafluoroethylene reactor with the conductive surface facing downward. After reacting at 160 °C for 24 h, the mixture was placed in a tubular furnace for phosphating. The hydrothermal sample and 142.2 mg of sodium hypophosphite powder were placed at both ends of a porcelain boat (sodium hypophosphite was at the upwind side). The temperature was raised to 330 °C at a rate of 5 °C / min and kept at this temperature for 1 h to obtain a nickel phosphide / cadmium sulfide heterojunction nanorod array composite material with a Ni2P loading of 3%.
[0051] Figures 1 to 5 The scanning electron microscope images of the nickel phosphide / cadmium sulfide heterojunction nanorod arrays prepared in Examples 1 to 5 are shown. It can be seen from the figure that the nickel phosphide presents a granular structure (circled) and is evenly attached to the cadmium sulfide nanorods, and the original rod-like structure of the cadmium sulfide nanorods is maintained (with a diameter of about 180 nm). At the same time, as the proportion of the phosphorus source in the reactants increases, the nanorod-like structure of the cadmium sulfide is not destroyed.
[0052] Figure 6 X-ray diffraction patterns of nickel phosphide / cadmium sulfide heterojunction nanorod arrays with different nickel phosphide loadings prepared in Examples 1 to 5. It can be found from the figure that the peak shape is basically attributed to cadmium sulfide (PDF#41-1049), while the amount of nickel phosphide loading is small and no corresponding characteristic peak is found. In addition, the peak position of the nickel phosphide / cadmium sulfide heterojunction with different loadings does not change significantly, but only changes in the peak intensity, indicating that the crystal structure of the sample can still be maintained stable after nickel phosphide doping.
[0053] The photoelectric performance test of the obtained nickel phosphide / cadmium sulfide heterojunction nanorod array composite material adopts a three-electrode system, that is, the FTO with nickel phosphide / cadmium sulfide heterojunction nanorod array grown on the surface is used as the working electrode, the 1×2 cm platinum sheet is used as the counter electrode, Ag / AgCl is used as the reference electrode, the quartz tank is used as the photoelectrochemical electrolysis cell, and 0.1 M Na2SO3 aqueous solution (pH = 6.8) is used as the electrolyte. The electrochemical tester uses a CHI660D electrochemical station (Shanghai Chenhua Instrument Co., Ltd.), the light source power is 500 W, and the light intensity is 100 mW·cm -2 , the illumination area is 0.5 cm 2The xenon lamp simulates sunlight and tests the current-time (it) curve. The test time is 0-400 s (the sample is first tested in dark conditions for 40 s to eliminate the effects of photogenerated ion accumulation in the environment before the test). After that, intermittent illumination is performed at intervals of 30 s. The current density and light intensity of the photoelectrode under monochromatic light irradiation are measured by a monochromator in conjunction with a photoelectrochemical workstation, and then according to the formula IPCE=(1240× J ph / λ × P momo )×100% to calculate the incident photon to current conversion efficiency of the sample (the test range is 200~800 nm).
[0054] Figure 7 The current-time (it) curves of nickel phosphide / cadmium sulfide heterojunction nanorod arrays with different nickel phosphide loadings prepared in Examples 1 to 5 are shown in the figure. It can be found that the photoelectric performance of the nickel phosphide / cadmium sulfide heterojunction nanorod array with 3% nickel phosphide loading is the best, which can reach 1.90A·cm -2 , which is higher than that of the CdS nanorod array without NiP loading (0.54 mA·cm -2 ).
[0055] Figure 8 The photoelectric conversion efficiency (ABPE) curve of 3% nickel phosphide loaded nickel phosphide / cadmium sulfide heterojunction nanorod array. As shown in the figure, pure cadmium sulfide has the highest ABPE efficiency of 0.22% near 0.70 V, while the 3% nickel phosphide loaded nickel phosphide / cadmium sulfide heterojunction nanorod array reaches the highest ABPE value of 0.69% near 0.62V.
[0056] Fig. 9 The graph is a photoelectric conversion efficiency (IPCE) curve of the nickel phosphide / cadmium sulfide heterojunction nanorod array prepared in the examples and comparative examples. It can be found from the figure and Table 1 that the nickel phosphide / cadmium sulfide heterojunction nanorod array loaded with 3% nickel phosphide prepared in Example 3 exhibits better photoelectrochemical performance.
[0057] Table 1 Comparison of IPCE of different NiP / CdS heterojunction nanorod arrays
[0058] Fig.10 The current-time (it) curves of the nickel phosphide loaded nickel phosphide / cadmium sulfide heterojunction nanorod array prepared in Example 3 and the nickel phosphide / cadmium sulfide heterojunction nanorod array prepared in the comparative example are shown in the figure. It can be found that the photoelectric performance of the nickel phosphide / cadmium sulfide heterojunction nanorod array loaded with 3% nickel phosphide prepared in the present invention is the best, which can reach 1.90A·cm-2 , which is higher than that of the nickel phosphide / cadmium sulfide nanorod arrays prepared by the thermal phosphorus method (0.78 mA cm -2 ).
[0059] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing a nickel phosphide / cadmium sulfide heterojunction nanorod array composite material, characterized in that: The following steps are involved: (1) Preparation of cadmium sulfide nanorod arrays: Cadmium nitrate, thiourea, L-cysteine and deionized water were mixed evenly, transferred to a polytetrafluoroethylene reactor, and immersed in the pretreated conductive glass FTO substrate. After hydrothermal reaction, the substrate was cooled to room temperature, and the conductive glass FTO substrate was taken out, cleaned, dried, and then annealed to obtain an FTO substrate with cadmium sulfide nanorod arrays grown on the surface. (2) Preparation of nickel phosphide / cadmium sulfide heterojunction nanorod array composite material: dissolve the phosphorus source, nickel source and sodium borohydride in ethylenediamine, stir evenly and transfer to a hydrothermal reactor, immerse the FTO substrate with cadmium sulfide nanorod array grown on the surface obtained in step (1), cool to room temperature after solvothermal reaction, take out, wash and dry.
2. The preparation method according to claim 1, characterized in that The pretreatment method of the conductive glass FTO substrate in step (1) is to first ultrasonically clean the conductive glass FTO substrate with a mixed solution of acetone, isopropanol and deionized water in a volume ratio of 1:1:1 for 60 minutes, then ultrasonically clean it with deionized water for 60 minutes, and dry it at 60°C for later use.
3. The preparation method according to claim 1, characterized in that: The molar ratio of cadmium nitrate, thiourea and L-cysteine used in step (1) is 1:1:0.
6.
4. The preparation method according to claim 1, characterized in that: The hydrothermal reaction in step (1) is first carried out at 160°C for 1 h, then the temperature is raised to 180°C and the reaction is continued for 2.5 h.
5. The preparation method according to claim 1, characterized in that The annealing treatment in step (1) is to increase the temperature to 400°C at a rate of 5°C / min and keep the temperature for 1 hour.
6. The preparation method according to claim 1, characterized in that: In step (2), the phosphorus source is sodium hypophosphite, and the nickel source is nickel chloride.
7. The preparation method according to claim 1, characterized in that: The molar ratio of the phosphorus source, the nickel source and the sodium borohydride used in step (2) is (5-25):1.4:
52.
8. The preparation method according to claim 1, characterized in that The temperature of the solvent thermal reaction in step (2) is 160°C and the time is 24 hours.
9. A nickel phosphide / cadmium sulfide heterojunction nanorod array composite material prepared by the method of claim 1, characterized in that: The loading amount of nickel phosphide in the composite material is 1wt%-5wt%.
10. Use of the nickel phosphide / cadmium sulfide heterojunction nanorod array composite material as claimed in claim 9 as a photoelectric catalyst.
Citation Information
Patent Citations
Preparation method of nickel phosphide cocatalyst by photodeposition on cadmium sulfide
CN110813335A
Preparation method of nickel-based phosphide with controllable composition
CN109647459A
Method for producing hydrogen from methanol
CN112479158A
Preparation method of nickel phosphide / CdxZn1-xS catalyst
CN112547102A
Cadmium sulfide-sulfur indium zinc heterojunction nanorod array composite material and preparation method thereof
CN114016077A